Bevacizumab, sorafenib tosylate, sunitinib and temsirolimus for renal cell carcinoma: a systematic review and economic evaluation - J Thompson Coon (Health Technology Assessment, 2010)
Objectives: To assess the clinical effectiveness and cost-effectiveness of bevacizumab, combined with interferon (IFN), sorafenib tosylate, sunitinib and temsirolimus in the treatment of people with advanced and/or metastatic renal cell carcinoma (RCC). Data sources: Electronic databases, including MEDLINE, EMBASE and the Cochrane Library, were searched up to September/October 2007 (and again in February 2008). Review methods: Systematic reviews and randomised clinical trials comparing any of the interventions with any of the comparators in participants with advanced and/or metastatic RCC were included, also phase II studies and conference abstracts if there was sufficient detail to adequately assess quality. Results were synthesised narratively and a decision-analytic Markov-type model was developed to simulate disease progression and estimate the cost-effectiveness of the interventions under consideration. Results: A total of 888 titles and abstracts were retrieved in the clinical effectiveness review, including reports of eight clinical trials. Treatment with bevacizumab plus IFN or sunitinib had clinically relevant and statistically significant advantages over treatment with IFN alone, in terms of progression-free survival and tumour response, doubling median progression-free survival from approximately 5 months to 10 months. Temsirolimus had similar advantages over treatment with IFN in terms of progression-free and overall survival, increasing median overall survival from 7.3 to 10.9 months [hazard ratio (HR) 0.73; 95% confidence interval (CI) 0.58 to 0.92)], as did sorafenib in comparison with best supportive care in terms of overall survival, progression-free survival and tumour response, with a doubling of progression-free survival (HR 0.51; 95% CI 0.43 to 0.60). However, the last was associated with an increased frequency of hypertension and hand–foot skin reaction compared with placebo. No fully published economic evaluations of any of the interventions could be located. However, estimates from the PenTAG model suggested that none of the interventions would be considered cost-effective at a willingness-to-pay threshold of £30,000 per quality-adjusted life-year (QALY). Estimates of cost per QALY ranged from £71,462 for sunitinib to £171,301 for bevacizumab plus IFN. Although there are many similarities in the methodology and structural assumptions employed by PenTAG and the manufacturers of the interventions, in all cases the cost-effectiveness estimates from the PenTAG model were higher than those presented in the manufacturers’ submissions. Cost-effectiveness estimates were particularly sensitive to variations in the estimates of treatment effectiveness, drug pricing (including dose intensity data), and health-state utility input parameters. Conclusions: Treatment with bevacizumab plus IFN and sunitinib has clinically relevant and statistically significant advantages over treatment with IFN alone in patients with metastatic RCC. In people with three of six risk factors for poor prognosis, temsirolimus had clinically relevant advantages over treatment with IFN, and sorafenib tosylate was superior to best supportive care as second-line therapy. The frequency of adverse events associated with bevacizumab plus IFN, sunitinib and temsirolimus was comparable with that seen with IFN, although the adverse event profile is different. Treatment with sorafenib was associated with a significantly increased frequency of hypertension and hand–foot syndrome. Estimates from the PenTAG model suggested that none of the interventions would be considered cost-effective at a willingness-to-pay threshold of £30,000 per QALY.